1997
DOI: 10.1002/(sici)1099-1395(199703)10:3<129::aid-poc884>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer in Organic Reactions

Abstract: Most organic bond-forming reactions can be described as nucleophile-electrophile combinations. For many of these reactions there have been discussions as to whether the bond formation occurs together with the electron transfer or whether electron transfer and bond formation take place in separate steps. This discussion is reviewed and it is shown how to distinguish between the different processes based on kinetic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…Quinones are well known to be electron acceptors with the formation of chargetransfer complexes. 43,44 Control experiments revealed that no reaction was observed on treatment of Mes 3 P with pO 2 C 6 Cl 4 in C 6 H 5 Cl. Moreover, the UV-visible ).…”
Section: Resultsmentioning
confidence: 99%
“…Quinones are well known to be electron acceptors with the formation of chargetransfer complexes. 43,44 Control experiments revealed that no reaction was observed on treatment of Mes 3 P with pO 2 C 6 Cl 4 in C 6 H 5 Cl. Moreover, the UV-visible ).…”
Section: Resultsmentioning
confidence: 99%
“…One is an electron-transfer mechanism where C 60 2- acts as an electron donor and the other is an S N 2 mechanism where C 60 2- acts as a nucleophile. The electron transfer vs nucleophilic process alternative has been one of the most central propositions in reaction mechanism, but it has never been examined in the case of C 60 . The heterogeneous electron-transfer reactions of fullerenes with electrodes 1 as well as their photoinduced electron-transfer reactions have been studied extensively, , but few studies have been carried out with respect to the homogeneous electron-transfer reactions of C 60 .…”
Section: Introductionmentioning
confidence: 99%
“…However, an intramolecular electron-transfer reaction of a donor-acceptor-linked system can also be started thermally by addition of a metal ion [22]. Addition of scandium triflate [Sc(OTf) 3 ] to an MeCN solution of ferrocene-naphthoquinone dyad (Fc-NQ) resulted in formation of the Fc + -NQ ؒ-/Sc 3+ complex as indicated by appearance of the absorption band due to the Fc + moiety at 860 nm together with the absorption band at λ max = 420 nm owing to the NQ ؒ-/Sc 3+ moiety (Scheme 5).…”
Section: Catalytic Control Of Intramolecular Electron Transfermentioning
confidence: 99%
“…1 and 5 [28]. Hydride transfer from AcrH 2 to 3,6-diphenyl-1,2,4,5-tetrazine (Ph 2 Tz), which contains N=N double bond, occurs efficiently in the presence of Sc(OTf) 3 via Sc 3+ -promoted electron transfer in MeCN at 298 K, whereas no reaction occurs in the absence of Sc 3+ [29].…”
Section: Catalytic Control Of Electron Transfer and The Subsequent Stepmentioning
confidence: 99%
See 1 more Smart Citation